UK QE reconsidered: the real economy effects of monetary policy inthe UK, 1990-2012 – an empirical analysis - Giovanni Bernardo; Josh Ryan‐Collins; Richard A. Werner (Centre for Banking, Finance and Sustainable Development - University of Southampton, 2013)
Empirical studies of so called ‘unconventional’ monetary policy – ‘Quantitative Easing’ or ‘Large Scale Asset Purchases’ - since the North Atlantic Financial Crisis of 2007-2009 in the United Kingdom and elsewhere have mainly focussed on the effect of policy on intermediate variables rather than the stated ultimate goal of such policies, boosting nominal demand and GDP growth. Secondly and relatedly they tend to focus on the crisis and post-crisis period, a time of extraordinary economic and financial dislocation, which creates counterfactual and attribution problems and fails to capture typical macroeconomic lag dynamics. Adopting the approach of Voutsinas and Werner (2010), and building on Lyonnet and Werner’s (2012) study of UK QE, this paper addresses these weaknesses by 1) examining the impact of various different monetary policy instruments (including Quantitative Easing) directly on UK nominal GDP growth; and 2) using a quarterly time series beginning in the first quarter of 1990 and up to the last quarter of 2012 (92 observations in total). We use the Hendry ‘general-to-specific’ econometric methodology to estimate a parsimonious model. The results show that disaggregated bank credit to the real economy (households and firms) has the most significant impact on nominal GDP growth. Changes to the central bank’s interest rate, central bank reserves, and total central bank asset ratios drop out of the model as insignificant. The policy implication it that, as private banks continue to shrink their balance sheets in the UK and Europe following the North Atlantic Crisis of 2008, central banks might wish to consider ‘unconventional’ monetary policies that more directly boost credit to the real economy and thus nominal GDP growth.